Corporate Governance, Ownership Structure, and IPO Underpricing: Evidence from the Indian New Issue Market - Singh, Amit Kumar; Maurya, Sheetal (Indian Journal of Research in Capital Markets, 2018)
This paper attempted to contribute to extant literature on IPO underpricing by examining the effect of corporate governance on IPO underpricing. Although, previous research in the field of corporate governance has already studied the role of effective corporate governance on several fronts, the role of corporate governance in abating information asymmetry and thereby signalling the value of firms to potential investors is an area that is yet to be explored (particularly in context of Indian new issue market). The results of the present study indicated that presence of independent directors on board was more informative than presence of non-executive directors ; also, merely meeting the regulatory requirement while determining the board composition did not send a quality signal. The results revealed that only those firms which go beyond the minimum regulatory requirements pertaining to corporate governance norms catch some attention of investors.